Fetal loss and maternal serum levels of 2,2',4,4',5,5'-hexachlorbiphenyl (CB-153) and 1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (p,p'-DDE) exposure: a cohort study in Greenland and two European populations - Ludwicki Jan K; Pedersen Henning S; Jönsson Bo A; Thulstrup Ane M; Toft Gunnar; Zvezday Valentyna; Bonde Jens P (BMC, 2010)
Abstract Background In the present study, the aim is to examine the risk of fetal loss related to environmental 2,2',4,4',5,5'-hexachlorobiphenyl (CB-153) or 1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene (p,p'-DDE) exposure. Methods We related LC/MS/MS measurements of CB-153 and p,p'-DDE in serum samples to interview-data on previous fetal loss in populations of pregnant women from Poland, Ukraine and Greenland. Results In total, 1710 women were interviewed, and 678 of these had at least one previous pregnancy. The risk of ever experiencing a fetal loss increased at higher levels of CB-153 and p,p'-DDE exposure, with an adjusted odds ratio (OR) of 2.4; confidence interval (CI) (1.1-5.5) for CB-153>200 ng/g lipid compared to 0-25 ng CB-153/g lipid and OR of 2.5 CI (0.9-6.6) for p,p'-DDE>1500 ng/g lipid compared to 0-250 ng DDE/g lipid. However, no clear dose response associations were observed. The results further suggest that high level of organochlorine serum concentrations may be related to repeated loss. Conclusions The risk of fetal loss may increase at higher levels of CB-153 and p,p'-DDE exposure, although lack of dose response and inconsistencies between countries did not allow for firm conclusions.